Representaciones sociales de docentes y estudiantes sobre la práctica docente que influyen la formación humanista en el ciclo V del Colegio Atanasio Girardot IED - Malpica Moreno, Diana María (Universidad de La Salle. Facultad de Ciencias de la educación. Maestría en Docencia (incluye Maestría en Docencia - CESMAG)., 2017)
The current research project is aimed at identifying the social representations of teachers and students in the teaching practice that influence the humanistic teaching in cycle V at the Atanasio Girardot School. In order to achieve this objective and given the qualitative nature of the research, it was required the implementation of the ethnographic method. It allowed us to understand the roles, values, behaviors and interests that emerge from the interaction among the teachers and students during teaching process. Two methodological approaches for data collection were required: the group interview and the observation. Their implementation enabled us to approach the targeted polulation, the teachers and students of cycle V. To process the data, it was required to implement the method of content analysis. It enabled us to determine that the elements of the social representations reviled by the teachers and students, which contribute to the teaching practice to become more human, are closely related to the “si” exam, sensitivity, ethical coherence, imagination, dialogic action and the interaction in the classroom. Thus in the pedagogical process, the representations, which are the result of the interaction among teachers and students are due to the reflective practice and emotional relationships. Likewise, it was found that the representations of the good teacher and the good student allow us to understand the humanistic teaching practice.